Teaching information seeking - Louise Limberg; Olof Sundin (Information Research: An International Electronic Journal)
Introduction. The article argues for a closer association between information seeking research and the practices of teaching information seeking. Findings are presented from a research project on information seeking, didactics and learning (IDOL) investigating librarians' and teachers' experiences of teaching information seeking. Method. Thirteen teachers and five librarians, teaching 12-19 year-old students in three schools, participated. Forty-five interviews were conducted over a period of three years. Analysis. The IDOL project adopted a phenomenographic approach with the purpose of describing patterns of variation in experiences. The findings were also analysed by way of relating them to four competing approaches to the mediation of information literacy. Results. A gap was identified between experiences of teaching content that focused on sources and order, and experiences of assessment criteria applied to students' work that focused on the importance of correct facts and the analysis of information. These findings indicate a highly restricted range of teaching contents when compared with the four theoretical approaches to the mediation of information literacy. Conclusion. Teaching information seeking might be enhanced by a wider repertoire of contents reflecting more varied theoretical understanding developed in information seeking research, particularly as regards the importance of content and context related to user perspectives.